In God We Trust: Community and Immunity in American Religions during COVID-19 - Julia Brown (Religions, 2023)
From the systemic issues of race and class division to political partisanship and religious identity, the pandemic has affected many aspects of American social and political life. I interrogate the role that religions have played in communal identity-making during the pandemic, and how such identities shaped ideological responses, particularly in the US, stymying public health efforts to stop, or at least significantly slow, the spread of COVID-19. Drawing from Gabriel Garcia Marquez’s Love in the Time of Cholera as a historical case study, I use Garcia Marquez’s depiction of religion’s identity-making power during the cholera pandemic depicted in the novel as a comparison by which to understand current experiences of white Evangelical Christians in America during the current COVID-19 pandemic, particularly those who reject risk-minimizing practices such as mask wearing, quarantining, and vaccination. Drawing both from representations of Roberto Esposito’s theory of immunity and community, and from Lauren Berlant’s concept of “cruel optimism”, as well as sociological understandings of religion and identity, I argue that the boundary-making practices of religion and of communal and national identity are related to the complex and often contradictory set of moral practices that led many white Evangelicals to disregard public health policies surrounding COVID-19. A concurrent analysis of Garcia Marquez’s novel and of current events will allow me to explore this phenomenon, as Lauren Berlant would put it, both through the historically affective aesthetic and through the affective present.